European incomes, national advantages: EU-wide inequality and its decomposition by country and region - Stefano Filauro (Economics and Econometrics Research Institute (EERI), 2017)
This study analyses EU-28- and euro area-level income distribution with the latest EU-SILC data. More specifically it shows the evolution of inequality in net disposable and market incomes over the pre- and post-crisis period (2006-2013). I find that inequality between the EU-28 and euro area (EA) has converged due to a slow decrease in EU-28 inequality, at least until 2009, coupled with a mild increase in EA inequality. Thus, I compute how much between-country inequality, as opposed to within-country inequality, contributes to overall inequality in the EU-28 and euro area, observing that the trend of between-country inequality, albeit starting from very different levels, has been declining in the EU-28 while slightly increasing in the euro area. Similar trends are observed for between-region inequality. Finally, I approximate the extent to which individual incomes on the European scale can be predicted by country of residence and find evidence in line with the inequality decomposition by country.
Keywords: D3; D63; O52; 330; Distribution; income inequality; decomposition by country; European Union; equality of opportunity